2018
DOI: 10.23913/ride.v9i17.387
|View full text |Cite
|
Sign up to set email alerts
|

La Inteligencia emocional y la práctica docente en profesores investigadores / Emotional Intelligence and teaching practice in research professor

Abstract: El presente artículo tiene el objetivo de estudiar las relaciones entre la inteligencia emocional y cinco factores que analizan la práctica docente en profesores de posgrado para identificar su comportamiento de acuerdo con  el género, la escolaridad, la pertenencia al Sistema Nacional de Investigadores (SNI). Se trata de  un estudio transversal cuantitativo; se aplicaron dos instrumentos: el primero mide la inteligencia emocional y el segundo estudia la práctica docente, la muestra productora de datos es de 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results of this research showed that, professors with a PhD degree exhibit a favorable relationship between the variables perception of emotions and their understanding and a positive relationship between the understanding and regulation of emotions; likewise, these authors identified the existence of a positive relationship between course planning and the class' planning and evaluation 13,20 .…”
Section: Sastre Castillo and Danvila Del Vallementioning
confidence: 77%
“…The results of this research showed that, professors with a PhD degree exhibit a favorable relationship between the variables perception of emotions and their understanding and a positive relationship between the understanding and regulation of emotions; likewise, these authors identified the existence of a positive relationship between course planning and the class' planning and evaluation 13,20 .…”
Section: Sastre Castillo and Danvila Del Vallementioning
confidence: 77%